Perencanaan Sistem Informasi Manufaktur Berbasis Engginering To Order dan Make To Order - Mauluddin, Yusuf; Kurniadi, Dede; Abdulah, Farhan Naufal (Jurnal Algoritma, 2024)
In fulfilling demand at PT. Garut Makmur Perkasa, the production process often experiences errors in recording and reporting, including in exchanging information between departments. This is caused by a lack of control in the recording process which still relies on manual methods and the absence of special procedures that regulate this process. Frequent errors in recording and reporting cause communication between departments to be hampered. Therefore, companies need Standard Operating Procedures (SOP) which regulate work procedures in the production process. To support this, an integrated information system is needed that can replace manual methods with digital methods. The method used in this research uses the waterfall method and SOP design uses the Cross Functional Flowchart method combined with narrative. This research only reaches the prototype stage of the manufacturing information system which was created using Canva web design simulation. This research produced a draft Standard Operating Procedure (SOP) for the production department, wetblue leather warehouse department, and finished goods warehouse department to help the company maintain employee consistency and performance. And a manufacturing information system to make it easier for employees to manage the recording process and exchange information between departments.